Facilitators and Barriers to Expedited Partner Therapy: Results From a Survey of Family Physicians. Issue 8 (August 2020) - Wong, Jason; Zakher, Bernadette; Consolacion, Theodora; Leong, Jeffrey; Choi, Alexandra; Prescott, Cheryl; Ng, Brian; Pawa, Jasmine; Campbell, Audrey
Abstract : Background: Expedited partner therapy (EPT) can prevent transmission of sexually transmitted infections (STIs) and reinfection of the index patient. We surveyed family physicians (FPs) in British Columbia to understand their perceptions of barriers and facilitators to EPT use and explored how perceptions varied by demographic and practice characteristics. Methods: Survey participants were recruited through the Divisions of Family Practice, which include greater than 90% of FPs in British Columbia. Common barriers and facilitators for EPT were identified using descriptive statistics. The association between each EPT barrier and facilitator and demographic and practice characteristics were tested using χ 2 test. Results: One hundred eighty-one FPs started the survey, of which 146 (80.7%) answered 10 questions or more and were analyzed. Overall, inaccurate information about sex partners (88 [60.3%] of 146) and medicolegal concerns (87 [59.6%] of 146) were the most common barriers reported. Family physicians in nonurban settings were more likely to identify insufficient time as a barrier compared with FPs in urban settings ( P < 0.01). The most common facilitators were having a health care professional for follow-up after prescribing EPT (110 [75.3%] of 146), improved remuneration (93 [63.7%] of 146), clear clinical guidelines around EPT (87/146, 59.6%), and having a legal framework (92 [63.0%] of 146). Family physicians practicing for less than 9 years (the median) were more likely to identify the latter as facilitating EPT compared with FPs practicing for 9 years or longer ( P < 0.05). Conclusions: Ensuring patients have access to a health care professional for follow-up, improved remuneration, and development of clinical guidelines and a legal framework can support the implementation of EPT. Tools catered to different practice types and contexts may help increase EPT use. Abstract : A survey of family physicians in Canada found that improved remuneration and development of clinical guidelines and a legal framework can support expedited partner therapy as an intervention to control sexually transmitted infections.